2016
DOI: 10.12660/bre.v99n992016.52273
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Brazilian Inflation with High-Dimensional Models

Abstract: In this paper, we use high dimensional models, estimated by the least absolute shrinkage and selection operator (LASSO) to forecast Brazilian inflation. The models are compared to benchmark specifications such as linear autoregressive (AR) and the factor models based on principal components. Our results show that the LASSO-based specifications have the smallest errors for short-horizon forecasts. However, for long horizons, the AR benchmark is the best model with respect to point forecasts, even though there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
(27 reference statements)
0
14
0
3
Order By: Relevance
“…The relevance of past inflation was also pointed out by Kohlscheen (2012). More recently, Medeiros, Vasconcelos, and Freitas (2016) considered different high-dimensional models for forecasting Brazilian inflation. The authors showed that techniques based on the least absolute shrinkage and selection operator (LASSO) have the smallest forecasting errors for short horizon forecasts.…”
Section: Introductionmentioning
confidence: 91%
“…The relevance of past inflation was also pointed out by Kohlscheen (2012). More recently, Medeiros, Vasconcelos, and Freitas (2016) considered different high-dimensional models for forecasting Brazilian inflation. The authors showed that techniques based on the least absolute shrinkage and selection operator (LASSO) have the smallest forecasting errors for short horizon forecasts.…”
Section: Introductionmentioning
confidence: 91%
“…Tradicionalmente, ao avaliar a capacidade preditiva de modelos previsores, a abordagem rolling window aparece como preferida (Medeiros et al, 2019;Medeiros, Vasconcelos e Freitas, 2015;Panagiotelis et al, 2019;Tarassow, 2019), pois atenua problemas relacionados a outliers e quebra estrutural. Além disso, ela produz série de erros preditivos em diferentes horizontes de previsão, utilizados na avaliação empírica dos modelos considerados, similar ao observado nas seções anteriores.…”
Section: Exercício De Previsão Pseudo Fora Da Amostraunclassified
“…Poucos trabalhos têm investigado o desempenho preditivo desses modelos no Brasil. Medeiros et al (2016), por exemplo, aplicam métodos shrinkage baseado no Lasso, para prever a taxa de inflação brasileira, mensurada pelo IPCA e IGP. Os autores mostram que este método gera melhores previsões que modelos autorregressivos.…”
Section: Introductionunclassified
“…A dinâmica das variáveis macroeconômicas em países emergentes, como o Brasil, apresenta características próprias que podem prejudicar o desempenho de modelos de previsão. Assim, espera-se que este trabalho contribua para gerar modelos de previsão mais adaptados ao comportamento das variáveis brasileiras, como em: Medeiros et al (2016), Garcia et al (2016), Ferreira, Bierens e Castelar (2005), entre outros. Além disso, este artigo contribui para compreensão de como modelos fatoriais podem ter seu poder preditivo melhorado ao se introduzirem técnicas de aprendizado estatístico como: Kim e Swanson 2014 O restante do artigo está organizado da seguinte forma: a seção 2 apresenta os modelos fatoriais e a forma pela qual métodos de aprendizagem estatística podem ser utilizados na previsão.…”
Section: Introductionunclassified